Clinical Study of 107 Hospitalized Patients with Peritonsillar Abscess - Wakisaka, Risa; Kumai, Takumi; Kishibe, Kan; Takahara, Miki; Katada, Akihiro; Hayashi, Tatsuya; Harabuchi, Yasuaki (International Journal of Practical Otolaryngology, 2021)
We conducted a retrospective analysis of the data of 107 cases of peritonsillar abscess treated at our hospital between January 2014 and December 2018. Data on age, sex, affected site, duration of hospitalization, method of drainage, presence/absence of laryngeal edema, antibacterial drugs used, and isolated bacteria were analyzed. Of the 107 patients, 71 were males and 36 were females; the median age was 44 years (range: 18–88 years).The left side was affected in 55 patients, the right side in 50 patients, and both sides in two patients. The abscess was localized in the superior pole in 71 patients, and in the inferior pole in 36 patients. Thirty-five patients had laryngeal edema, of which three underwent tracheotomy. Recurrence of the abscess was observed in 15 cases, with the recurrence developing within 3 months in 7 cases, and over a period of 3 years in 4 cases. As for the sensitivity of the causative bacteria to antibacterial drugs, 17% of the causative bacteria showed resistance to clindamycin, while none showed resistance to ampicillin/sulbactam (ABPC/SBT). We concluded that ABPC/SBT might be suitable for the initial treatment of peritonsillar abscess, and that we need to bear in mind the possibility of long-term recurrence.
Keywords: peritonsillar abscess; laryngeal edema; recurrence